Direct Synthesis and Pseudomorphic Transformation of Mixed Metal Oxide Nanostructures with Non‐Close‐Packed Hollow Sphere Arrays. Issue 48 (2nd November 2018) - Liu, Zhendong; Zhao, Wenyang; Kumar, Prashant; Li, Xinyu; Al Wahedi, Yasser; Mkhoyan, K. Andre; Tsapatsis, Michael; Stein, Andreas
Abstract: While bottom‐up syntheses of ordered nanostructured materials at colloidal length scales have been successful at producing close‐packed materials, it is more challenging to synthesize non‐close‐packed (ncp) structures. Here, a metal oxide nanostructure with ncp hollow sphere arrays was synthesized by combining a polymeric colloidal crystal template (CCT) with a Pechini precursor. The CCT provided defined confinement through its tetrahedral (Td ) and octahedral (Oh ) voids where the three‐dimensionally (3D) ordered, ncp hollow sphere arrays formed as a result of a crystallization‐induced rearrangement. This nanostructure, consisting of alternating, interconnected large and small hollow spheres, is distinct from the inverse opal structures typically generated from these CCTs. The morphology of the ncp hollow sphere arrays was retained in pseudomorphic transformations involving sulfidation and reoxidation cycling despite the segregation of zinc during these steps. Abstract : Airy architecture : A new concept for the fabrication of nanostructures featuring 3D ordered, non‐close‐packed hollow sphere arrays is demonstrated through controlling dynamic changes in interfacial properties between template and precursor. The polymeric colloidal crystal provides defined confinement through its tetrahedral and octahedral voids where the arrays are formed as a result of a crystallization‐induced rearrangement.